2007
DOI: 10.1007/s00221-007-1075-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial memory enhances the precision of angular self-motion updating

Abstract: Humans are typically able to keep track of brief changes in their head and body orientation, even when visual and auditory cues are temporarily unavailable. Determining the magnitude of one's displacement from a known location is one form of self-motion updating. Most research on self-motion updating during body rotations has focused on the role of a restricted set of sensory signals (primarily vestibular) available during self-motion. However, humans can and do internally represent spatial aspects of the envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 31 publications
1
40
1
Order By: Relevance
“…Vision of the environment was provided before each body rotation, but the rotations themselves were administered without vision. The rotations were delivered using a computer-controlled device described elsewhere [78]. The velocity profile was roughly triangular, and consisted of an initial acceleration of 90°/s 2 up to a peak velocity of 54, 81, and 90°/s for the 30°, 75°, and 120° rotations, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Vision of the environment was provided before each body rotation, but the rotations themselves were administered without vision. The rotations were delivered using a computer-controlled device described elsewhere [78]. The velocity profile was roughly triangular, and consisted of an initial acceleration of 90°/s 2 up to a peak velocity of 54, 81, and 90°/s for the 30°, 75°, and 120° rotations, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has shown that visual preview can sometimes facilitate spatial updating in a blind-walking task. 40,41 Our blind subjects showed no consistent preview benefit. This may not be surprising, given that their preview was limited to auditory cues.…”
Section: Discussionmentioning
confidence: 62%
“…In contrast, for the experimenter-guided walking task, no information regarding the upcoming trajectory (i.e., walking distance) was given. Previous research has shown that vision of target locations and salient landmarks while viewing the environment provides contextual information for self-motion updating tasks (Arthur et al , 2007, 2009; Philbeck et al , 2001). It has been speculated that specifically the anticipation of actively walking to a predetermined location forms the basis of the spatiotemporal framework for incoming sensory signals during goal-directed linear locomotion (Philbeck et al , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our test environment afforded participants with a highly structured context (well-lit hallway, pictures on the walls). Previous work has validated that previewed landmarks along linear and angular trajectories do facilitate path integration, even when the observer cannot directly sense the objects as they pass (Arthur et al , 2007, 2009; Israël et al , 1996; Philbeck and O’Leary, 2005; Philbeck et al , 2001). However, the contextual information was available to participants in both the target-directed and experimenter-guided tasks.…”
Section: Discussionmentioning
confidence: 99%